1999
DOI: 10.33584/rps.7.1999.3403
|View full text |Cite
|
Sign up to set email alerts
|

The impact of endophyte on the health and productivity of sheep grazing ryegrass-based pastures

Abstract: The health and production of sheep grazing perennial ryegrass with and without wild-type endophyte (Neotyphodium lolii) has been studied in several trials over a number of years. Lambs/ hoggets grazing predominantly perennial ryegrass swards with endophyte developed moderate to severe ryegrass staggers in summer and autumn, while those grazing endophyte-free ryegrass did not. Lambs/hoggets grazing ryegrass with endophyte also had more dags, lower growth rates, lower plasma prolactin levels, higher body tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 24 publications
0
16
1
Order By: Relevance
“…Although this trial utilised a diet containing both ergovaline and lolitrem B, it nevertheless highlights that sheep can exhibit heat stress symptoms even under thermoneutral conditions. Heat stress, measured as increased body temperature and respiration rate, at ambient temperatures in Canterbury, New zealand, during summer/autumn, has been reported in sheep grazing ryegrass with standard endophyte (Fletcher 1998;Fletcher et al 1999) (Table 4). Furthermore, although rectal temperature of lambs increased with increasing ambient temperature the rectal temperature of lambs grazing ryegrass infected with the 187BB endophyte which had higher concentrations of ergovaline (and no lolitrem B) were consistently higher compared to lambs grazing ryegrass infected with the standard endophyte, which had lower concentrations of ergovaline but did contain lolitrem B, as well as animals grazing endophyte-free ryegrass which contained no toxins (Figure 3).…”
Section: Sheepmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this trial utilised a diet containing both ergovaline and lolitrem B, it nevertheless highlights that sheep can exhibit heat stress symptoms even under thermoneutral conditions. Heat stress, measured as increased body temperature and respiration rate, at ambient temperatures in Canterbury, New zealand, during summer/autumn, has been reported in sheep grazing ryegrass with standard endophyte (Fletcher 1998;Fletcher et al 1999) (Table 4). Furthermore, although rectal temperature of lambs increased with increasing ambient temperature the rectal temperature of lambs grazing ryegrass infected with the 187BB endophyte which had higher concentrations of ergovaline (and no lolitrem B) were consistently higher compared to lambs grazing ryegrass infected with the standard endophyte, which had lower concentrations of ergovaline but did contain lolitrem B, as well as animals grazing endophyte-free ryegrass which contained no toxins (Figure 3).…”
Section: Sheepmentioning
confidence: 99%
“…Heat stress symptoms have been observed to be more severe in lambs forced to graze lower into the sward (Bluett et al 1999). Fletcher et al (1999) concluded from a review of results across New Zealand that heat stress in lambs and sheep due to ergovaline would be especially prevalent in the warm humid conditions of northern New Zealand. Fletcher et al (1991) in a trial in Canterbury demonstrated that after 14 days lambs grazing ryegrass infected with either standard endophyte or 187BB endophyte gained less weight than lambs grazing on endophyte-free ryegrass although only the lambs grazing the standard endophyte treatment lost weight after 28 days.…”
Section: Sheepmentioning
confidence: 99%
“…The use of a high-endophyte ryegrass was expected to further impede animal performance on the control treatment. Fletcher et al (1999) recorded suppressions in lamb summer/ autumn liveweight gains ranging from 20 to 185 g/d owing to the presence of endophyte in ryegrass.…”
Section: Animal Performancementioning
confidence: 99%
“…Lamb liveweight gain has been reported (Fletcher et al 1999) to have been reduced by up to 10 g/d in summer and autumn, for every 10% increase in endophyte infection, though there was variation between years and localities. The range in individual liveweight gains in the present study was large (-82 to 238 g/d), possibly precluding detection of any overall relationship between pasture mix (and thus endophyte) and liveweight gain.…”
Section: Figurementioning
confidence: 99%
“…This neurological disorder is characterised by uncoordinated movement and loss of appetite (Keogh 1973), and is often seen in stock grazing perennial ryegrass dominant pastures. Cattle, sheep, deer and horses are susceptible, with affected sheep having significantly reduced liveweight gains (Fletcher 1983;Fletcher & Borrell 1984;Fletcher et al 1999). Furthermore, these animals are difficult to move, and may become immobile and occasionally die of starvation, dehydration or misadventure.…”
Section: Introductionmentioning
confidence: 99%